Follow-Up Study of Youth Who Received EIBI as Young Children. Issue 2 (March 2019) - Perry, Adrienne; Koudys, Julie; Prichard, Alice; Ho, Hilda
Although early intensive behavioral intervention (EIBI) has been clearly shown to be evidence-based, there is very little information available regarding long-term outcomes, especially from community effectiveness studies. We present data on cognitive, adaptive, and autism severity measures from four time points (pre- and post-EIBI and two follow-up points) for a sample of 21 youth, currently aged 16 years on average (range = 13-20) who received EIBI as young children and who have been out of EIBI for a mean of 10 years (range = 8.5-14). Results show heterogeneous outcomes and a general pattern of stability since the end of EIBI, suggesting gains made in EIBI are maintained.